2018
DOI: 10.4143/crt.2017.252
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Surgical Timing on Pathologic Tumor Response after Short Course and Long Course Preoperative Chemoradiation for Locally Advanced Rectal Adenocarcinoma

Abstract: PurposeA pooled analysis of multi-institutional trials was performed to analyze the effect of surgical timing on tumor response by comparing short course concurrent chemoradiotherapy (CCRT) with long course CCRT followed by delayed surgery in locally advanced rectal cancer.Materials and MethodsThree hundred patients with cT3-4N0-2 rectal adenocarcinoma were included. Long course patients from KROG 14-12 (n=150) were matched 1:1 to 150 short course patients from KROG 10-01 (NCT01129700) and KROG 11-02 (NCT01431… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 33 publications
(48 reference statements)
0
10
0
2
Order By: Relevance
“…). A total of 26 publications, including four RCTs and 25 445 patients with rectal cancer were eligible for inclusion ( Table ). Twenty‐four of the 26 studies (22 650 patients) reported the primary endpoint of pCR based on the predefined wait interval and were included in the qualitative and quantitative analysis for this outcome variable; 15·9 per cent (1522 of 9551) and 11·3 per cent (1481 of 13 099) had achieved pCR in the extended and classical intervals respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…). A total of 26 publications, including four RCTs and 25 445 patients with rectal cancer were eligible for inclusion ( Table ). Twenty‐four of the 26 studies (22 650 patients) reported the primary endpoint of pCR based on the predefined wait interval and were included in the qualitative and quantitative analysis for this outcome variable; 15·9 per cent (1522 of 9551) and 11·3 per cent (1481 of 13 099) had achieved pCR in the extended and classical intervals respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐four of the 26 studies (22 650 patients) reported the primary endpoint of pCR based on the predefined wait interval and were included in the qualitative and quantitative analysis for this outcome variable; 15·9 per cent (1522 of 9551) and 11·3 per cent (1481 of 13 099) had achieved pCR in the extended and classical intervals respectively. All patients underwent neoadjuvant 5FU‐based (5FU–capecitabine–folinic acid) nCRT, except in seven trials that included some patients treated with concomitant oxaliplatin (5 trials) or irinotecan (2) in addition to 5FU or had a proportion of patients who had nSCRT (1 trial). The number of participants in the included trials ranged from 31 to 16 915; apart from the RCTs and one phase II non‐randomized trial, all were retrospective or prospective observational series.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve studies (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25), with a total of 1,723 participants, reported a reduction in T or N stage based on the pretreatment clinical staging by CT or MRI versus the final pathological staging. As shown in figure 2.2, significant heterogeneity was observed (I 2 = 79%, p < 0.05) and a random effect model was applied.…”
Section: Tumor Downstaging Ratementioning
confidence: 99%
“…Probst et al, хоть и ретроспективного, на выборке в 17 255 больных показано, что частота полных патоморфологических эффектов была значимо выше при интервале между двумя методами лечения более 8 недель в сравнении с интервалом в 6 недель -13,2% против 8,7%, р < 0,001 [26]. Аналогичные находки описаны и в отношении короткого курса предоперационной лучевой терапии (5 х 5 Гр) [27]. Выявленные закономерности особенно актуальны в контексте возможности наблюдения за пациентами, у которых достигнут полный клинический эффект.…”
Section: ранний рак толстой кишкиunclassified